EVALUATION AND DETERMINATION OF TRAMADOL AND METHADONE IN VITREOUS SAMPLES WITH THE AID OF DISPERSIVE LIQUID-LIQUID MICROEXTRACTION- HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Badakhshan, Dariush; Ramezani , Majid (Journal of the Chilean Chemical Society, 2020)
In the present work, the use of microextraction methods for the separation and pre-concentration of narcotic drugs in urine and vitreous samples is presented. These simple and eco-friendly methods are used to measure tramadol and methadone, which are used to relieve pain and treat addiction to other drugs. Urine and vitreous samples from 54 corpses referenced to legal medicine were analyzed by high performance liquid chromatography. Extraction of tramadol and methadone was performed separately using 200 μl chloroform, 700 μl methanol at pH 10. Under the optimum conditions, the detection limit linear range were obtained 4.5 µg L-1and 1.2 µg L-1 , 4.5-1000 µg L−1 and 1-1000 µg L−1for determination of tramadol and methadone, respectively. According to the results, for accurate interpretation of the methadone and tramadol concentration in the bodies, its measurement in vitreous fluid is very useful and practical.